PENERAPAN HUKUM KELUARGA MUSLIM DI ASIA TENGGARA - Anam, Ahmad Khoirul (Direktorat Jenderal Bimbingan Masyarakat Islam, 2017)
Family law applied in a country shows how the religion position in the legal system and government in the country. Marriage and its intricacies are state affairs, as well as religious affairs. So the issue of family law is almost always a land of contention for the state and religion. The following article will compare the Muslim family law application in countries in Southeast Asia, the most populous Muslim region in the world. How is the Islamic law application in Muslim-majority countries such as Indonesia, Malaysia and Brunei Darussalam? How is the Muslim family law application in Muslim countries such as Singapore, the Philippines and Thailand, and the fate of the Muslim community in the Indo-China region: Myanmar, Vietnam, Cambodia and Laos. The condition of the